Efficiency Evaluation of Primary and Secondary Education Sector Performance in East Java Using Data Envelopment Analysis - Bahalwan Apriyansyah; Syarifa Hanoum; Prahardika Prihananto; Siti Lailatul Mukaromah (Jurnal Sosial Humaniora, 2020)
Education has an important role in creating excellent human resources forthe advancement of national development. However, in Indonesia, there arestill gaps in equal access to education. This study aims to evaluate theperformance efficiency of the education sector to provide recommendationsof which considered inefficient by using the Data Envelopment Analysis(DEA) method. This study measures the technical efficiency of primary andboth secondary schools (junior and senior high School) in 38 regencies/citiesin East Java Province for three academic years (2016-2019). The resultsshowed that technical inefficiency still occurs in the implementation ofeducation in East Java. In addition, peer groups and improvement targetswere obtained for the inefficient regencies/cities. The indicators that mostinfluence the efficiency value of the education sector in East Java are theEducation Fund Allocation as the input variable and the School ContinuingRate as the output variable. The scale efficiency analysis shows that most ofthe education sector in East Java operates in decreasing returns to scale.